Behaviour-based price discrimination with elastic demand - Esteves, Rosa Branca (2012)
Behaviour-based price discrimination is typically analysed in a framework characterised by inelastic demand. This paper provides a first assessment of the role of elastic demand on the competitive effects of behaviour-based price discrimination. Our results show that if demand is elastic enough, behaviour-based price discrimination leads to demand expansion which has a positive effect on overall welfare.